ANALISIS KESULITAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL - Musrifa Peka; Ratna Abdul Pakdin Balikh; Fadhillah Abdul Halik Likur; Mukmin Amsidi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze students’ difficulties in solving problems of systems of linear equations in two variables and to identify the factors causing these difficulties among eighth-grade students at UPTD SMP Negeri Anlawening. This research employed a qualitative approach with a case study design. The research subjects consisted of 22 students, with 6 students selected as samples through purposive sampling. Data were collected through observation, interviews, and documentation. The data were analyzed using descriptive qualitative analysis techniques, including data reduction, data display, and conclusion drawing. The results of the study indicate that students experience various difficulties in solving problems of systems of linear equations in two variables, including difficulties in conceptual understanding, arithmetic operations, understanding word problems, applying solution methods, and remembering formulas. The factors causing these difficulties consist of internal factors, such as low learning interest, motivation, and basic mathematical skills, as well as external factors, such as an unconducive learning environment and lack of parental support. Efforts to overcome these difficulties include providing regular practice exercises, applying individual approaches, using varied teaching methods, and fostering collaboration among teachers, students, and parents. ABSTRAK Penelitian ini bertujuan untuk menganalisis kesulitan peserta didik dalam menyelesaikan soal sistem persamaan linear dua variabel serta mengidentifikasi faktor-faktor penyebabnya pada peserta didik kelas VIII UPTD SMP Negeri Anlawening. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Subjek penelitian berjumlah 22 peserta didik, dengan sampel sebanyak 6 peserta didik yang dipilih secara purposive sampling. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan teknik analisis deskriptif kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa peserta didik mengalami berbagai kesulitan dalam menyelesaikan soal sistem persamaan linear dua variabel, meliputi kesulitan dalam pemahaman konsep, operasi hitung, memahami soal cerita, penggunaan metode penyelesaian, serta daya ingat terhadap rumus. Faktor penyebab kesulitan terdiri dari faktor internal, seperti rendahnya minat belajar, motivasi, dan kemampuan dasar matematika, serta faktor eksternal, seperti lingkungan belajar yang kurang kondusif dan kurangnya dukungan orang tua. Upaya yang dapat dilakukan untuk mengatasi kesulitan tersebut antara lain pemberian latihan soal secara rutin, pendekatan individual, penggunaan metode pembelajaran yang variatif, serta kerja sama antara guru, peserta didik, dan orang tua.